Elongated oligonucleotide-linked immunosorbent assay for sensitive detection of a biomarker in a microwell plate-based platform - Han, Ki-Cheol; Yang, Eun Gyeong; Ahn, Dae-Ro (ELSEVIER ADVANCED TECHNOLOGY, 2013)
The immunoassay is a representative method for detecting disease biomarkers and pathogenic biological agents. While the conventional enzyme-linked immunosorbent assay (ELISA) has been routinely used for the analysis of biological samples, methods with higher sensitivity are still in demand because the detection of low-level biomarkers is important for early diagnosis of lethal diseases. In this study, we developed a sensitive immunoassay called elongated oligonucleotide-linked immunoassay (EOLISA), employing long DNA oligonucleotides (80-mer), a fluorogenic RNA probe and RNase H for signal amplification. The elongated DNA oligonucleotides led to a highly amplified fluorescence signal via iterative cycles of DNA-RNA duplexation and subsequent degradation of the RNA in the duplex by RNase H. The immunoassay was evaluated for sensitive detection of fatty acid binding protein (FABP) in the 0-1 ng mL(-1) range. When compared with ELISA, EOLISA showed about 10-fold improved detection sensitivity. With its simple procedure and reliable detection performance in the conventional platform, the proposed immunoassay is expected to have potential applications in clinical diagnostics. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: ANTIGEN; AMPLIFICATION; IMMUNOASSAYS